We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
109
1
avatar+397 

deleted.

 Jun 9, 2019
edited by sinclairdragon428  Nov 20, 2019
edited by sinclairdragon428  Nov 21, 2019
 #1
avatar+104963 
+3

3y^2 + 5y + 2  = 4

 

3y^2 + 5y - 2  = 0

 

(3y - 1) (y + 2)  = 0

 

Set each factor to 0...solve for y

 

3y - 1 = 0             y + 2 = 0

3y =1                    y = - 2

y =1/3

 

 

y = -2  is the least  value

 

 

cool  cool  cool

 Jun 9, 2019

27 Online Users

avatar